Mobility and resource use influence the occurrence of pollinating insects in restored seminatural grassland fragments. Issue 5 (13th December 2017) - Öckinger, Erik; Winsa, Marie; Roberts, Stuart P. M.; Bommarco, Riccardo
Abstract: After habitat restoration, species need to recolonize from existing populations. The ability of species to recolonize restored habitats likely depends on their traits. This study aimed to test if species traits and isolation from source habitat can explain the presence of insects in restored grasslands. We surveyed the occurrence of hoverflies and bees in 14 restored seminatural pastures as well as in intact seminatural grasslands in the surrounding landscape. We tested how connectivity, time since restoration, and species traits influence if species that are present in the surrounding landscape also occur in restored pastures. Solitary bee species present in the landscape were less likely to occur in restored pastures compared to bumblebees and hoverflies. The occurrence of bumblebees, but not solitary bees or hoverflies, decreased with time since restoration. The occurrence of solitary bees increased but the occurrence of hoverflies decreased with high connectivity. Migratory hoverflies were more likely to occur in restored pastures than nonmigratory hoverflies, especially in pastures with low connectivity. Among both bumblebees and solitary bees, the occurrence was influenced by nesting traits, with the lowest occurrence of parasitic species and of species digging nests in the ground. The subset of the landscape's species pool that occurs in restored pastures has a contrasting set of traits compared with species in intact source habitats. Both mobility and resource use act as filters that influence the assembly of pollinator communities after restoration. A full recovery of pollinator communities is more likely if source populations are available nearby.